DESIGN AND EVALUATION OF CLOUD COMPUTING NETWORK SECURITY USING NETWORK DEVELOPMENT LIFE CYCLE METHOD AT PT. XYZ - Gautama Wijaya; Franky Viky Franklyn (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Cloud computing is an internet-based service model for accommodating enterprise resources where companies do not have to think about resources because cloud computing service providers provide resource facilities on the internet. Because the resources of cloud computing systems on the internet, as well as providing services to many people simultaneously, can allow cloud computing systems to be easily threatened by various types of Cyber Attacks. The purpose of this research is to develop the design of a secure cloud computing network architecture using the NDLC method by developing a cloud computing network security system using IDPS case study technology at PT. XYZ. IDPS Snort is used as an intrusion detection and prevention system as well as a firewall to filter packet packets that are indicated as threats. The evaluation was conducted to prove whether the network security system applied to cloud computing technology can run well, by testing several attacks such as Ports Scanning using NMAP, Ping of Death and DoS SYNFlood. The results of the evaluation proved that IDPS SNORT can detect and block all well-tested attacks on the applied cloud computing network.